Recent trends in stature of 14-year-old boys from Wrocław, Poland - Kołodziej, Halina; Kozieł, Sławomir (Anthropological Review, 2002)
The aim of this study was to investigate the educational groupspecific secular trends in stature of 14-year-old boys from Wrocław. The study was based on two cohorts of boys measured in 1987 and 1997. On the basis of mother and father education level divided into three categories, social sub-groups were selected. During the period 1987-97 the mean stature of 14-year-old boys has risen from 163.6 cm in 1987 to 165.6 cm in 1997. Growth trends were positive in all sub-groups selected on the basis of father education. The analysis of secular changes in body height within the separated social sub-groups showed that boys whose fathers had a university education were the tallest and boys whose fathers had basic vocational or elementary school education were the shortest. The greatest increment in body height (2.82 cm) took place in the sub-group of boys whose fathers had secondary school education. In all of the sub-groups selected on the basis of mother education the growth trends were positive. The boys from the sub-group where the mother had secondary school education experienced the largest increment in body height during the period 1987-97.